Foucault y la psicología: la ventana indiscreta: Foucault and psychology: the undiscrete window - FOLLARI, Roberto (Utopía y Praxis Latinoamericana, 2021)
RESUMEN Foucault golpeó fuertemente a la Psiquiatría con su Historia de la locura. Mostró los minuciosos ejercicios de violencia que en el Hospital General de París se daban en nombre de la ciencia y la normalidad. Del rechazo a tal normalidad, se dio su rechazo al psicoanálisis, entendido como normalizador. Desde su estetización de la locura, asumida con el discurso revelador de la Anti-razón moderna, pasó a la consideración del dispositivo psicoanalítico como análogo al de la confesión cristiana, y a la creencia de que el peso dado culturalmente al sexo no devenía de pulsiones, sino que era puro efecto discursivo. ABSTRACT Foucault hit Psychiatry hard with his History of Madness. He showed the meticulous exercises of violence that took place in the General Hospital of Paris in the name of science and normality. From the rejection to such normality, he gave his rejection to psychoanalysis, understood as normalizing. From his aestheticization of madness, assumed as the revealing discourse of modern Anti-reason, he passed to the consideration of the psychoanalytic device as analogous to that of the Christian confession, and to the belief that the cultural weight given to sex did not come from drives, it was purely discursive effect.